Electrosprayed whey protein-based nanocapsules for β-carotene encapsulation. (1st June 2020) - Rodrigues, Rui M.; Ramos, Philippe E.; Cerqueira, M.F.; Teixeira, José A.; Vicente, António A.; Pastrana, Lorenzo M.; Pereira, Ricardo N.; Cerqueira, Miguel A.
Highlights: Whey protein isolate (WPI) loaded with beta-carotene were produced by electrospray. Electrospray process was improved by presence of ethanol. The increase of ethanol concentration from 5 to 15% had an effect on the protein unfolding. The rehydrated capsules present higher sizes than the dried capsules obtained after electrospray. Abstract: In this work an electrohydrodynamic process (electrospray) was used to produce β-carotene loaded nanocapsules based on whey protein isolate (WPI). WPI solutions were prepared in aqueous solutions with different concentrations of ethanol (5, 10 and 15%) which were used for β-carotene solubilization. Different electrospray conditions were tested and the morphology and molecular organization of the nanocapsules were studied on dried and hydrated state. The size of the dried nanocapsules ranged between 227 and 283 nm. After hydration, there was a significant increase in the mean size of the nanocapsules, being the sizes higher for nanocapsules produced with increasing concentrations of ethanol. Results, obtained from the reactivity of free sulfhydryl groups and fluorescence analysis, showed that the increase of ethanol concentration had a destabilizing effect on the protein unfolding. Electrosprayed WPI-based nanocapsules can be used for the encapsulation of β-carotene answering the industrial demand for novel encapsulation technologies to protect sensitive bioactive compounds.